2022
DOI: 10.1177/17407745221110880
|View full text |Cite
|
Sign up to set email alerts
|

A platform trial design for preventive vaccines against Marburg virus and other emerging infectious disease threats

Abstract: Background: The threat of a possible Marburg virus disease outbreak in Central and Western Africa is growing. While no Marburg virus vaccines are currently available for use, several candidates are in the pipeline. Building on knowledge and experiences in the designs of vaccine efficacy trials against other pathogens, including SARS-CoV-2, we develop designs of randomized Phase 3 vaccine efficacy trials for Marburg virus vaccines. Methods: A core protocol approach will be used, allowing multiple vaccine candid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 19 publications
2
21
0
Order By: Relevance
“…Our results suggest that the vast majority of future outbreaks may have no cases in both the vaccine and placebo arms, and would in fact be controlled before VE estimations could begin (ten days after implementing the vaccination campaign, which is when cases are included in any VE calculations). It was previously calculated that 150 cases, both in the vaccine and control arms, would be required to estimate VE (8). Figure 2 shows a histogram of the number of simulated MVD outbreaks required to reach 150 combined cases in the vaccine and placebo arms.…”
Section: Discussionmentioning
confidence: 99%
“…Our results suggest that the vast majority of future outbreaks may have no cases in both the vaccine and placebo arms, and would in fact be controlled before VE estimations could begin (ten days after implementing the vaccination campaign, which is when cases are included in any VE calculations). It was previously calculated that 150 cases, both in the vaccine and control arms, would be required to estimate VE (8). Figure 2 shows a histogram of the number of simulated MVD outbreaks required to reach 150 combined cases in the vaccine and placebo arms.…”
Section: Discussionmentioning
confidence: 99%
“…Although efforts are ongoing to develop MVD vaccines (4), the results of our study suggest that it may be difficult to carry out Phase 3 trials, since we predict that few cases will be observed in a typical outbreak, and these may well be rapidly controlled by other interventions. To counter this problem, the World Health Organisation has developed a Core Protocol approach that is designed to allow trial results to be combined across multiple outbreaks to accrue sufficient data and statistical power to assess vaccine effectiveness (26, 29). There has also been a recent paper from WHO on a core protocol for estimating Marburg virus vaccine efficacy (29).…”
Section: Discussionmentioning
confidence: 99%
“…To counter this problem, the World Health Organisation has developed a Core Protocol approach that is designed to allow trial results to be combined across multiple outbreaks to accrue sufficient data and statistical power to assess vaccine effectiveness (26, 29). There has also been a recent paper from WHO on a core protocol for estimating Marburg virus vaccine efficacy (29). The results of our model could be helpful in estimating how many cases and outbreaks may be necessary to include in such a longitudinal multi-outbreak study.…”
Section: Discussionmentioning
confidence: 99%
“…Such a subunit (recombinant) vaccine platform can thereby help in developing multivalent vaccine candidates for protecting against filoviruses while retaining their safety and efficacy (Lehrer et al 2021). Few other vaccines being tried include multi-epitope vaccine, proteomebased vaccine exploiting computational methods, virus-like particles (VLP), adenoviral vector-based multi-filovirus vaccine, rprotein based filovirus multivalent vaccine, and rVSV-based vesiculovax vector vaccine (rVSV-N4CT1-MARV-GP), and efforts are being made for effective platform designing of preventive MVD vaccines (Reynolds and Marzi 2017;Hasan et al 2019;Suschak and Schmaljohn 2019;Dulin et al 2021;Lehrer et al 2021;Sami et al 2021;Longini et al 2022;Sebastian et al 2020;Soltan et al 2022;Woolsey et al 2022;Zhao et al 2022). Another candidate vaccine (recombinant VSV/ rVSV-based) known as PHV01 has been tested in the guinea pig model for confirming the efficacy (protective effects) against MVD (Zhu et al 2022).…”
Section: Treatment and Vaccinesmentioning
confidence: 99%